The Broadway song : a singer's guide - Clark, Mark Ross, 1951- (Oxford University Press, 2015)
Truly powerful vocal performance in musical theater is more than just the sum of good vocal tone and correct notes. As experienced teacher, director, and performer Mark Ross Clark lays out in The Broadway Song, powerful performance communicates the central function of a song within the context of the surrounding narrative, or the ""truth"" of a song. Because unstaged performances of a song, such as auditions, are key to the success of all aspiring singers, Clark provides here the essential practical manual that will help performers choose the right pieces for their vocal abilities and identify.